Anatomical and optical parameters and aberrations of the optical system of the eye in anisometropic myopia - V. V. Neroev; E. P. Tarutta; N. V. Khodzhabekyan; A. T. Khandzhian; S. G. Harutyunyan (Российский офтальмологический журнал, 2023)
Purpose: to compare anatomical and optical parameters and aberrations of both eyes in patients with acquired and congenital anisometropic myopia.Material and methods. 22 patients (44 eyes) aged 18–35 (averagely, 25.2) with acquired and congenital anisometropic myopia were examined using the Galilei G6 optical eye system analyzer (Ziemer, Switzerland). The analysis of total, corneal and internal aberrations of the eye was carried out on an OPD-Scan III (Nidek) aberrometer.Results. In both groups with acquired and congenital anisometropic myopia, the axial length of the higher myopic eye was greater than that of the fellow eye. A greater asphericity and higher astigmatism of the cornea were revealed in higher myopic eyes of patients with congenital myopia as compared to acquired myopia. The total RMS HOA in congenital myopia was significantly greater in the higher myopic eye compared to the fellow eye (1.07 D and 0.68 D, respectively) and greater than in cases of acquired myopia. All HOA were greater in higher myopic eyes as compared to the fellow ones in cases of congenital myopia. In case of acquired myopia only the total coma appeared to be greater in the higher myopic eye. Corneal aberrations in acquired anisometropic myopia did not differ in the paired eyes. In case of congenital myopia, the total tilt was significantly greater in the higher myopic eye, and total coma and spherical aberration have lower values, even with a transition to negative ones (p < 0.05).Conclusion. The revealed differences of the wavefront of the eyes with anisometropic congenital and acquired myopia are rather a consequence of anatomical and optical differences (the axial length of the eyes and the topography of the cornea), than the cause of anisometropia.